1999
DOI: 10.1109/51.775487
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine by mobile communication

Abstract: ulti~le ~u t u ~runsmissi~n from s in ~mergency Medicine ~ituutionshere have been many studies that have proved the feasibility and usefulness of telemedicine [ 1-31. Remote diagnosis of an ECG through a telephone network is a well-known example [4]. Telemedicine is a useful technique and has been used in such applications as medical care in remote rural areas and aftercare for pacemaker-implanted patients. However, the use of telemedicine has not spread as extensively as other commonly used engineering techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…Many research projects have reported success in building telemedicine systems using different technologies to enable on-scene EMS staff to consult with specialists in a remote location. Some examples are [1]- [4]. In our pilot studies, the successful implementation of telemedicine systems for EMS, offering synchronous-often referred to as real-timetelemedical consultation functionality, has been demonstrated [5], [6].…”
Section: Introductionmentioning
confidence: 87%
“…Many research projects have reported success in building telemedicine systems using different technologies to enable on-scene EMS staff to consult with specialists in a remote location. Some examples are [1]- [4]. In our pilot studies, the successful implementation of telemedicine systems for EMS, offering synchronous-often referred to as real-timetelemedical consultation functionality, has been demonstrated [5], [6].…”
Section: Introductionmentioning
confidence: 87%
“…Also, the mobile phone has been recognized as a possible tool for telemedicine since it became commercially available. This system which allows patients to measure their own vital signs, such as Heart Rate, temperature and provide the health care professionals with the facility to remotely monitor the patient's vital signs quickly and easily, vital signs can be transmitted from an ambulance to a hospital in a store-and forward mode [7], [8], or in real-time mode [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although store-and-forward ECG transmission is also possible from the ambulance to the hospital, real-time ECG monitoring by a cardiologist in a hospital would be more convenient because it allows a reduction in the time needed for patient's evaluation once it arrives to the hospital. These effects are specially crucial in cases where the transportation time is long [6], [7].…”
Section: Introductionmentioning
confidence: 99%